2018
DOI: 10.21100/jeipc.v4i1.706
|View full text |Cite
|
Sign up to set email alerts
|

A Platform for Partnership: A Technology Review of the Padlet sharing platform.

Abstract: Since technology permeates every aspect of contemporary life, just navigating Higher Education (HE) in the 21st century makes you, to an extent, ‘tech savvy’. However, when looking to technology to assist student/staff partnerships, colleagues need to take their practice beyond Microsoft Office, social media and Photoshop.During a student/staff partnership research project, a student and a higher education professional used the online platform Padlet as their selected medium for collaboration, in order to repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The author describes the tool by recommending it, but does not perform any qualitative or quantitative analysis. In other publications concerning Padlet we find a qualitative approach, which very positively assesses the role and use of Ppadlet in work at a university (Lowe & Humphrey, 2018). A quantitative approach, on the other hand, was taken up in research conducted by D. Dewitt and D. Alias (Dewitt, Alias, & Siraj, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…The author describes the tool by recommending it, but does not perform any qualitative or quantitative analysis. In other publications concerning Padlet we find a qualitative approach, which very positively assesses the role and use of Ppadlet in work at a university (Lowe & Humphrey, 2018). A quantitative approach, on the other hand, was taken up in research conducted by D. Dewitt and D. Alias (Dewitt, Alias, & Siraj, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Given the groups' comments on writing processes, it was revealed that 2 nd group students focused more on harmony and social interaction in the writing process, while the 1 st group made achievement-based comments. Upon reviewing the literature, online writing activities mostly involved process-oriented actions, perspectives and comments rather than the achievement of writing product, which is proximal to the perspective of 2 nd group students (DeWitt, Alias & Siraj, 2015;Ellis, 2015;Fisher, 2017;Fuchs, 2014;Hadjerrouit, 2011;Kessler & Bikowski, 2010;Lowe & Humphrey, 2018). Based on this, positive group interaction, democratic participant and contribution of each member should all be highlighted for online collaborative writing activities.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…like Google Docs that allow text document editing within the platform without the need for downloading), lack of notification and "folder" functions for easy filing and categorisation (e.g. Dropbox/OneDrive) are among the downsides of Padlet and could consequently result in students' negative perception of its use (Lowe & Humphrey, 2018).…”
Section: Discussionmentioning
confidence: 99%